The Development of Powerpoint-iSpring Learning Media on Electrolysis Cell Topic for Class XII SMA/MA - Mella Andriani; Guspatni Guspatni (Entalpi Pendidikan Kimia, 2022)
Electrolysis cell material is a chemical material that requires a correct understanding of the concept because it has a fairly high level of abstraction. The abstraction of a material presented can be helped by using media that can display three levels of chemical representation. PowerPoint-iSpring as a learning media can contain text, images, videos, animations and quizzes to help students understand chemistry. This study aims to develop PowerPoint-iSpring learning media on electrolysis cell material for class XII SMA/MA and determine the level of validity of the developed media. This study uses the Plomp research model to be carried out until the prototype stage 3 (one to one evaluation and expert review). The PowerPoint-iSpring learning media was validated by 5 material validators and 3 media expert validators. The research instrument used was a material validity sheet containing content validity and construct validity, as well as a media expert validity sheet. The results of the experimental data processing of the validity test used the Aiken's V formula. The results showed that the validity value of PowerPoint-iSpring learning media on the electrolysis cell material developed was valid for each item on the content, construct, and media components.